2022
DOI: 10.3390/molecules27123837
|View full text |Cite
|
Sign up to set email alerts
|

Potential Application of Gambogic Acid for Retarding Renal Cyst Progression in Polycystic Kidney Disease

Abstract: Abnormal cell proliferation and accumulation of fluid-filled cysts along the nephrons in polycystic kidney disease (PKD) could lead to a decline in renal function and eventual end-stage renal disease (ESRD). Gambogic acid (GA), a xanthone compound extracted from the brownish resin of the Garcinia hanburyi tree, exhibits various pharmacological properties, including anti-inflammation, antioxidant, anti-proliferation, and anti-cancer activity. However, its effect on inhibiting cell proliferation in PKD is still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…GA has been shown to inhibit the proliferation of melanoma (95), esophageal squamous carcinoma (99), and glioma cells (100). Khunpatee et al (32) studied the effect of GA on ADPKD in MDCK and PKD1 mutant cells. The results showed that GA inhibits the enlargement of cysts by inhibiting the phosphorylation of the ERK1/2 and mTOR/S6K signaling pathways (32).…”
Section: Gambogic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…GA has been shown to inhibit the proliferation of melanoma (95), esophageal squamous carcinoma (99), and glioma cells (100). Khunpatee et al (32) studied the effect of GA on ADPKD in MDCK and PKD1 mutant cells. The results showed that GA inhibits the enlargement of cysts by inhibiting the phosphorylation of the ERK1/2 and mTOR/S6K signaling pathways (32).…”
Section: Gambogic Acidmentioning
confidence: 99%
“…( 32 ) studied the effect of GA on ADPKD in MDCK and PKD1 mutant cells. The results showed that GA inhibits the enlargement of cysts by inhibiting the phosphorylation of the ERK1/2 and mTOR/S6K signaling pathways ( 32 ). In addition, GA can significantly improve the phosphorylation activity of AMPK ( 32 ).…”
Section: The Effect Of Plant-derived Compounds In Adpkd Modelsmentioning
confidence: 99%